2021
DOI: 10.1080/13676261.2021.1965106
|View full text |Cite
|
Sign up to set email alerts
|

Towards a culturally situated understanding of bullying: viewing young people’s talk about peer relationships through the lens of consent

Abstract: Bullying has typically been defined and studied separately from other forms of gender-and sexuality-related harassment and violence such as dating and relationship violence and sexual harassment, arguably obscuring the complex interrelations between these phenomena. This article is based on an EU-funded project which explored young people's understandings and experiences of sexual bullying (bullying related to gender and/or sexuality). Data collected via 41 focus groups with young men and women (N = 253) aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Por otra parte, se hace necesario destacar que el acoso de contenido sexual fue el tercero más observado, presente en un 9,71% de los escolares, lo que hace relevante explorar a profundidad estos comportamientos y las características tanto de las víctimas como de quienes protagonizan estos actos, ya que es un problema complejo que puede estar influenciado por roles de dominación y poder sobre el otro (Milnes, et al, 2022), por lo que es necesario el abordaje mediante acciones preventivas y de intervención por parte de los diversos actores de la comunidad educativa en busca de la reparación de la víctima, garantías de no repetición y la consolidación de un clima escolar basado en el respeto mutuo.Los hallazgos encontrados en este estudio refuerzan la necesidad de establecer acciones que incrementen los niveles de AF y que reduzcan las cifras de AE en las instituciones educativas, haciendo énfasis especialmente en las adolescentes y en las instituciones de carácter oficial; esto debido a la importancia de promover una cultura que valore las características personales del estudiante, sus diferencias en el aprendizaje y las realidades contextuales, y que se utilicen herramientas de carácter ético, emocional y social para abordar estas problemáticas en la educación física.…”
Section: Discussionunclassified
“…Por otra parte, se hace necesario destacar que el acoso de contenido sexual fue el tercero más observado, presente en un 9,71% de los escolares, lo que hace relevante explorar a profundidad estos comportamientos y las características tanto de las víctimas como de quienes protagonizan estos actos, ya que es un problema complejo que puede estar influenciado por roles de dominación y poder sobre el otro (Milnes, et al, 2022), por lo que es necesario el abordaje mediante acciones preventivas y de intervención por parte de los diversos actores de la comunidad educativa en busca de la reparación de la víctima, garantías de no repetición y la consolidación de un clima escolar basado en el respeto mutuo.Los hallazgos encontrados en este estudio refuerzan la necesidad de establecer acciones que incrementen los niveles de AF y que reduzcan las cifras de AE en las instituciones educativas, haciendo énfasis especialmente en las adolescentes y en las instituciones de carácter oficial; esto debido a la importancia de promover una cultura que valore las características personales del estudiante, sus diferencias en el aprendizaje y las realidades contextuales, y que se utilicen herramientas de carácter ético, emocional y social para abordar estas problemáticas en la educación física.…”
Section: Discussionunclassified
“…In line with this, despite a few sexual consent educational programmes recognising the role of the wider social systems which shape young people's experiences and understandings of consent (Burton et al 2021), this is particularly important when it comes to addressing power inequalities within sexual relationships (Jones, Milnes, and Turner-Moore 2021). It is crucial that the societal and systemic nature of power imbalances are unpacked in discussion with young people (Jones, Milnes, and Turner-Moore 2021), in order to encourage young people to reflect on the power and privilege they may access at a structural level and how this subsequently may serve as a barrier for others to communicate their discomfort or non-consent (Milnes, Turner-Moore, and Gough 2021). Whilst sexual violence is gendered (Muehlenhard et al 2017), the findings here often illustrated a reluctance to acknowledge gendered power and privilege when it comes to sexual consent.…”
Section: Discussionmentioning
confidence: 99%
“…One of the themes, The Nature of Sexual Bullying, encapsulated two subthemes: what constituted 'sexual bullying' according to young people (Milnes et al, 2021), and the diverse forms of sexual bullying reported by them, including the varied acts that the young people had experienced or witnessed that they presented as examples of sexual bullying. It is this second subtheme, Diverse Forms of Sexual Bullying, that was most relevant to the present study, and thus, we re-read all the extracts coded under this subtheme and considered how they illustrated and explained the quantitative analyses.…”
Section: Qualitative Datamentioning
confidence: 99%